Ethical Tourism Consumption: Should Businesses Be Concerned? - Mokoena, Lehlohonolo Gibson (African Journal of Hospitality, Tourism and Leisure, 2019)
Negative socio-cultural, economic and environmental impacts of tourism continue to be a major concern. This concern has led to the number of initiatives aimed at creating awareness about tourist activities and the overall impact of tourism on the environment and society in general. This awareness has already started to have an effect on the way in which some tourists behave, how they select tourism products and destinations. This wave of awareness may in the future also compel tourism businesses to operate businesses differently, in a profitable way whilst ensuring the minimisation of the negative impacts of tourism. This paper focuses on addressing the possible impact of alarming tourism markets on the negative socio-cultural, economic and environmental issues caused by the tourism industry and it addresses the impact this awareness may have on tourism businesses currently lacking corporate social responsibility (CSR) initiatives. This paper thus draws the attention of ethical tourism to businesses and reinforces the importance and implications thereof. Ethical tourism strives to maximise the positive impacts of tourism, and simultaneously tries to minimise the destructive impacts. The concept of ethical tourism also means that purchasing decisions of tourism consumers will include an element of responsible consumption. This in turn will mean that businesses without ethical credentials will be less competitive, should this “new tourist” phenomenon gain traction. The paper encourages that the tourism industry should lead the way in terms of responsible tourism, not solely for the purpose preparing for the ethical tourism market in the future and being competitive, but because it is about protecting and improving the future of the tourism industry sustainably.
Published Article
Keywords: Environment; Tourism; Negative Impacts; Ethical Consumption; Tourist